Soft Actuation of Structured Cylinders through Auxetic Behavior2. Issue 6 (13th January 2015) - Lazarus, Arnaud; Reis, Pedro M.
<x xml:space="preserve">Abstract</x> We introduce a new class of soft actuators based on the buckling of locally patterned elastic cylindrical shells that can be designed to reversibly achieve flexural or twisting motion. Depressurizing our samples allows for tunable and controllable motion. Given that the deformation is primarily governed by geometry and elasticity, the resulting modes of actuation should be readily scalable.